1992
DOI: 10.1164/ajrccm/146.3.790
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Maximal Respiratory Mouth Pressures: A Population-based Study

Abstract: The aim of our study was to measure values of maximal inspiratory (MIP) and expiratory (MEP) mouth pressures in 625 (266 male, 359 female) clinically and functionally normal subjects drawn out of a sample representative of the general population. MEP (near TLC and FRC) was found to be significantly higher when compared with MIP (near RV and FRC), and pressures in male subjects were significantly higher than those in female subjects. MEP values at TLC and FRC were found to be closely related, as were values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
104
2
17

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 4 publications
7
104
2
17
Order By: Relevance
“…Both smokers and nonsmokers were included in this study. In line with the literature on reference values [4,5,7,8], smoking status was not significant in predicted values of MIP and MEP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both smokers and nonsmokers were included in this study. In line with the literature on reference values [4,5,7,8], smoking status was not significant in predicted values of MIP and MEP.…”
Section: Discussionsupporting
confidence: 90%
“…Portable devices are useful for rapid and simple assessment of respiratory function in the office and at the bedside. Prediction values of spirometry and maximal respiratory pressures are available for portable and nonportable devices with a standard tube or a flanged type of mouthpiece connection [4][5][6][7][8]. This equipment is only suitable for subjects capable of making a good seal with their lips around the mouthpiece.…”
mentioning
confidence: 99%
“…We believe that the reductions in MRP, found for every two and three decades in both males and females, may be due to the aging process, a fact which is made more evident by the negative correlation verified between age and RMS. The negative correlations found between age and MRP for both sexes were high and corroborate the results found by Neder et al 1 and Vincken, Ghezzo and Cosio 24 , but diverge from those of Bruschi et al 26 and McElvaney et al 27 . Various hypotheses have tried to explain this negative correlation.…”
Section: Discussionsupporting
confidence: 86%
“…The American Thoracic Society and the European Respiratory Society 22 reported that the variations between the MIP and MEP values reported by several authors presumably indicates differences among the groups studied and in the way the tests were carried out and measured. Bruschi et al 23 described that in the past twenty years different studies on maximal respiratory pressure were published and they displayed a great variability in the results. These authors reported that the variability could be attributed to the different methodologies used, as well as the kind of mouthpiece, number of maneuvers performed, body position, and differences inherent to the studied populations.…”
Section: Discussionmentioning
confidence: 99%